Associated factors for HIV and syphilis infection among men who have sex with men only and men who have sex with both men and women in cities of China. (April 2013) - She, M; Zhang, H; Wang, J; Xu, J; Zhang, Z; Fan, Y; Sun, Y; Zhang, C
Summary: The aims of this paper were to find out the status of HIV and syphilis infection and to examine the sexual behaviours between men who have sex with men only (MSM/M) and men who have sex with both men and women (MSM/W), as well as to determine the correlates for HIV and syphilis infection among MSM/M and MSM/W, respectively. Among 1693 MSM who participated in the study, the proportions of MSM/M and MSM/W were 82.1% and 17.9%, respectively. The prevalences of HIV infection were 7.0% in MSM/M and 6.6% in MSM/W and the prevalences of syphilis infection were 11.9% and 13.2%, respectively. Among the MSM/M subset, the correlates both for HIV and syphilis infection included having more sexual partners, and being receptive or both insertive and receptive for anal sex. Among the MSM/W subset, living in Chengdu was associated with HIV infection and using condoms inconsistently during anal sex was associated with syphilis infection. The findings of this survey call for interventions tailored according to the needs of different subsets of MSM.